The Sabu Tribe's Concept of Culture and Traditions Through the Perspective of Feminist Theology - Wila, Amelia; Tari, Ezra; Revilla, Abdiel Enrique Sánchez (Sekolah Tinggi Teologi Simpson Ungaran, 2025)
This research examines the culture and traditions of the Sabu tribe through a feminist theological perspective to understand how women are positioned in a social system that is often associated with patriarchy. Although injustice against women is still found in various cultural practices in Indonesia, research findings show that the puru tradition actually presents the value of equality and respect. Using a descriptive qualitative method, this study found that puru functions as a protection mechanism for women from harassment, prejudice, and immoral acts. This tradition is in line with the Christian teaching of God's just love and respect for human dignity. Through puru, Sabu women gain space to determine their own way of life, develop as a whole person, and enjoy equal rights with men. Thus, women are seen as independent individuals and have control over their existence and future.